Pengaruh Rasio-rasio Keuangan terhadap Harga Saham Sektor Agrikultur di Bursa Efek Indonesia Periode 2014-2018 - Abqari, Lingga Sundagumilar; Hartono, Ulil (Universitas Negeri Surabaya, 2020)
The objectives to be achieved by this research are knowing the effect of the ratio of return on equity, earnings per share, price earning ratio, and the debt to equity ratio to stock prices in the agricultural sector on the Indonesia Stock Exchange in the 2014-2018 period. This study has a population that is used namely agricultural sector companies recorded on the Stock Exchange in the 2014-2018 period upwards of 17 companies. Multiple linear regression analysis methods were utilized in this study. Based on conclusions, there is a negative effect of the ratio of return on equity (X1) to stock prices (Y) in the first hypothesis test. For the subsequent hypothesis testing the conclusions indicate that the earnings per share ratio (X2) has a positive effect on stock prices (Y). This study also found that the price earning ratio (X3) harmed stock prices (Y) in the third hypothesis test. While the fourth hypothesis test shows that the debt to equity ratio (X4) does not affect stock prices (Y). This happens because of the movement of each variable on stock prices.